Virtual Laboratory: An Alternative Method of Practicum Learning in Higher Education during the Covid-19 Pandemic - Muslim, Abd. Qadir; Hermawan, Hermawan; Cahyasari, Erlita; Fanani, Muhammad Adip (Journal of Education Technology, 2022)
The practicum laboratory is one of the crucial factors in lectures whose practice is still experiencing many obstacles during the pandemic in Indonesia. Due to online learning regulations that require students not to be active in campus laboratories. This research with an R&D approach aims to produce e-learning products based on virtual laboratories and meet the limited access to practicum laboratories. This study involved 101 students who were used as respondents and research subjects. With an R&D approach and using the Rowntree development model, the product is refined at a level. In the first stage, the research team conducted a preliminary study to photograph student learning models in the industrial 4.0 era amid the COVID-19 pandemic. The second stage is to create an e-learning model based on a virtual laboratory with Zoom in quantitative research methods courses using SPSS software. In this study, the research team designed two versions of the training model, which were consulted with experts and then revised based on the consultation results. Small-scale and large-scale product testing was carried out by the team research so that, in the end, the virtual laboratory product was obtained in the final. In the post-test assessment, the research results positively prove that 99% of students agree with the existence of virtual laboratory-based e-learning. Based on these results, a virtual laboratory must be immediately created through e-learning or online learning supported by an active learning approach so that students will be able to practice quantitative data analysis optimally using SPSS.